1999
DOI: 10.1046/j.1365-2052.1999.00453.x
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of bovine microsatellite markers for population genetic studies on African buffalo (Syncerus caffer)

Abstract: The applicability of bovine autosomal microsatellite markers for population genetic studies on African buffalo was investigated. A total of 168 microsatellite markers were tested for PCR amplification on a test panel of seven African buffalo. Amplification was observed for 139 markers (83%), and 101 markers were studied further with 91 (90%) being polymorphic. The mean number of alleles per marker was 5.0 (SE = 0.2) and the mean heterozygosity per marker was 0.61 (SE = 0.03). Considering the overall high level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 46 publications
4
21
1
1
Order By: Relevance
“…In the opposite, Arora et al (2004) found a low level of variability in river buffalo populations in the North of India. Other authors also have also studied genetic differences among buffalo populations using microsatellites (Van Hooft et al, 1999;Moioli et al, 2001;Navani et al, 2002 andFlamand et al, 2003). In Brazil, Baio and Carabao are small populations forming a pilot genetic conservation project developed by the Eastern Amazonia EMBRAPA in the Pará state.…”
Section: Discussionmentioning
confidence: 99%
“…In the opposite, Arora et al (2004) found a low level of variability in river buffalo populations in the North of India. Other authors also have also studied genetic differences among buffalo populations using microsatellites (Van Hooft et al, 1999;Moioli et al, 2001;Navani et al, 2002 andFlamand et al, 2003). In Brazil, Baio and Carabao are small populations forming a pilot genetic conservation project developed by the Eastern Amazonia EMBRAPA in the Pará state.…”
Section: Discussionmentioning
confidence: 99%
“…The high PCR amplification success could likely be attributed to the correspondence of the aligned filtered reads to highly conserved sequences. Van Hooft et al (1999) previously demonstrated high genome conservation when using microsatellites primers developed for cattle on African buffalo, with 83% successful amplification.…”
Section: Model Species Reference Genome and Snp Validationmentioning
confidence: 99%
“…The positive amplification rate in Saola (96.8%) is higher compared with other species of the subfamily Bovinae previously reported, for example African buffalo ( Syncerus caffer 83%, Van Hooft et al. 1999) and water buffalo ( Bubalus bubalis 70%, Moore et al.…”
Section: Discussionmentioning
confidence: 57%
“…1997), goat ( Capra hircus , Pepin et al. 1995), African buffalo ( Syncerus caffer , Van Hooft et al. 1999) and water buffalo ( Bubalus bubalis , Moore et al.…”
Section: Introductionmentioning
confidence: 99%